Etiology and antimicrobial susceptibility pattern in children with community acquired urinary tract infection - Wathore, Sandeep N.; Wade, Poonam (International Journal of Contemporary Pediatrics, 2021)
Background: Urinary tract infection (UTI) is represented as one of the most common disease encountered in medical practice today, occurring from neonate to geriatric age group. It is an important cause of morbidity in children and affects up to 10% of the childhood population. Methods: After properly cleaning ano-genital area, in infants and young children up to 3 years of age, urine sample was collected in proper aseptic way. Midstream urine sample were collected from children older than 3 years in a sterile container. Isolation of bacteria was done on blood agar and MacConkey agar using semi quantitative methods. Antibiotic sensitivity test was carried out by disc diffusion method using Mueller-Hinton (MH) agar. Results: Over a study period of eighteen months, one hundred eighty diagnosed cases of culture positive UTI were recruited in our study. It was found that UTI was more commonly seen in females than males with male to female ratio of 0.8:1. It was more commonly seen in children with age group from one month to one year of age and least commonly seen in children’s above 4 years of age. Most commonly isolated microorganism on urine culture was Escherichia Coli (86.7%), followed by Klebsiella pneumonae (11.7%). Maximum sensitivity was to nitrofurantoin (95%) as oral antibiotics and to meropenem (97.8%) for intravenous use. Ampicillin and cefotaxime were the least sensitive antibiotics. Conclusions: E. coli was the most common uropathogen for UTI. Nitrofurantoin and meropenam were the antibiotics with maximum sensitivity.